2013
DOI: 10.1155/2013/417928
|View full text |Cite|
|
Sign up to set email alerts
|

Crocus sativusL. (Saffron) Stigma Aqueous Extract Induces Apoptosis in Alveolar Human Lung Cancer Cells through Caspase-Dependent Pathways Activation

Abstract: Worldwide, lung cancer is the most common form of cancer. Saffron has been used in folk medicine for centuries. We investigated the potential of saffron to induce cytotoxic and apoptotic effects in lung cancer cells (A549). We also examined the caspase-dependent pathways activation of saffron-induced apoptosis against the A549 cells. A549 cells were incubated with different concentrations of saffron extract; then cell morphological changes, cell viability, and apoptosis were determined by the normal invertmicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 41 publications
1
61
0
3
Order By: Relevance
“…Protective effects of these interventions probably perform through the decreasing of glucose and HbA1c levels in blood of rats suffering from diabetes. Samarghandian et al (2013) showed that saffron induces apoptosis in alveolar human lung cancer cells through caspase-dependent pathways activation.…”
Section: Introductionmentioning
confidence: 99%
“…Protective effects of these interventions probably perform through the decreasing of glucose and HbA1c levels in blood of rats suffering from diabetes. Samarghandian et al (2013) showed that saffron induces apoptosis in alveolar human lung cancer cells through caspase-dependent pathways activation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study have revealed that proliferation of such cells was decreased after treatment of saffron in a dose-and time-dependent manner. 77 Moreover, saffron induced morphological changes, decreases percentage of some viable cells, and induce apoptosis. 77 Result of study revealed that crocin inhibited cell proliferation and induced apoptosis and cell cycle arrest at G 0 /G 1 phase.…”
Section: Anti-tumour Activitymentioning
confidence: 99%
“…[ Based on result study concluded that both saffron extract as well as crocin can inhibit cell proliferation and arrest cell cycle progression [77] Prostate cancer Cytotoxic and apoptosis induction…”
Section: Referencementioning
confidence: 99%
“…1 Šafran (Crocus sativus) dovodi do morfološke promene i apoptoze kulture ćelija humanog alvelarnog tumora (bazalnih epitelijalnih ćelija), aktivacijom kaspaza-zavisnog mehanizma. [3][4][5] Gugulsteron je glavni aktivni sastojak smole biljke Commiphora wightii (sin. C. mukul) za koji je utvrđeno da suprimira nastanak i rast tumora.…”
Section: Molekulski Mehanizmi Delovanja Biljnih Antitumorskih Supstanciunclassified
“…Posebno je proučavan mehanizam antitumorskog delovanja na kanceru pluća. [3][4][5] Tradicionalna upotreba nekih smola Commiphora vrsta (Commiphora wightii, sin. C. mukul) je bila najčešća u kombinacijama biljaka koje koristi Ajurvedska medicina.…”
unclassified